Apparent diffusion coefficient histogram analysis for predicting neoadjuvant chemoradiotherapy response in patients with rectal cancer - Andelib Babatürk; Ayşe Erden; İbrahim Ethem Geçim (Diagnostic and Interventional Radiology, 2022)

(untitled)
PURPOSEThis study aimed to retrospectively evaluate the apparent diffusion coefficient (ADC) histograms in predicting chemoradiotherapy (CRT) response in patients with locally advanced rectal cancer (LARC).METHODSA total of 51 patients who underwent surgery in our institution for rectal cancer following neoadjuvant CRT between November 2013 and July 2019 were enrolled. Conventional magnetic resonance (MR) and diffusion-weighted images obtained before and after CRT were evaluated retrospectively. All tumor-containing regions of interests were drawn in 3 selected axial images, and special software for histogram analysis was used to evaluate ADC distribution. ADC cutoff values from post-CRT ADC histogram were calculated from receiver operating characteristic (ROC) analysis for evaluating CRT response.RESULTSIn histopathological analysis, 5 patients (9.8%) had minimal response (group 1), 31 patients (60.8%) had partial response (group 2), and 15 patients (29.4%) had complete or almost complete response (group 3). In the ADC histogram, minimum, maximum, 10th, 25th, 50th, 75th, and 90th percentile, mean ADC values, and skewness values of groups 2 and 3 showed significant changes before and after CRT, but no difference was found within group 1 values. The mean, 25th, 50th, 75th percent ADC values after CRT and skewness, and kurtosis values were significantly different between group 1 and group 3. Skewness value from the ADC histogram in postCRT magnetic resonance imaging had the best diagnostic performance with an area under the ROC curve of 0.851 (P =.003) for detecting group 3. The skewness cutoff calculated from the ROC analysis was 0.210 for evaluating CRT response. The sensitivity and specificity of the cut-off value were 100% and 61.4%, respectively.CONCLUSIONThe ADC histogram analysis seems to have potential application in predicting response to neoadjuvant CRT in patients with locally advanced rectal cancer.